THE EFFECTIVENESS OF THE TRADITIONAL GAME TUK TUK GENI IN STIMULATING THE SOCIAL EMOTIONAL DEVELOPMENT OF CHILDREN AGED 5-6 YEARS AT TK RAUDHATUL HUDA, KEDAI RUNDING SOUTH ACEH - Liza Fidiawati; Kiki Safitri; Aprian Subhananto; Riza Oktariana; Fitriani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Social-emotional skills are still lacking and still need improvement.These symptoms are evidenced by the presence of several children whoare not yet able to interact well with themselves and their environment,and children are also unable to work together, control their emotions, andhelp fellow friends. The aim of this research is to determine the effectivenessof the traditional game Tuk-Tuk Geni to improve the social emotionality ofchildren aged 5-6 years at TK Raudhatul Huda Kedai Runding South Aceh.This research uses a quantitative type of research with an experimental onegroup pre-test post-test design method. Sample of 15 children, data collectionwas carried out through observation and data was analyzed using statistics. Theresearch results found that the Tuk Tuk Geni game was very effective inimproving children's social and emotional well being. This is proven by theaverage value of the pre-test activity results obtained at 10.5 and the post-testobtained at 13. The results of this research indicate that the Tuk Tuk Geni gamecan improve children's social emotional development as intended by thehypothesis results ttabel dapat dihitung dengan kriteria pengambilan keputusannilai thitung -26.00 and the significant value (2-tailed) is ≤ 001 with the df valueobtained from 15-1=25, the value obtained ttabel that is 1,761. So it can beconcluded that the value thitung ≥ ttabel =(-35.546 ≥ 1,761) then H1 is accepted and Ho is rejected, so it can be concluded "there is significant effectiveness betweenthe Tuk Tuk Geni game in improving the social emotions of children aged 5-6years at TK Raudhatul Huda.